Psychiatric comorbidity distribution and diversities in children and adolescents with attention deficit/hyperactivity disorder: a study from Turkey - YÃ¼ce,Murat; Zoroglu,SÃ¼leyman Salih; Ceylan,Mehmet Fatih; Kandemir,Hasan; Karabekiroglu,Koray (Neuropsychiatric Disease and Treatment, 2013)
Murat Yüce,1 Süleyman Salih Zoroglu,2 Mehmet Fatih Ceylan,3 Hasan Kandemir,4 Koray Karabekiroglu5 1Department of Child and Adolescent Psychiatry, Faculty of Medicine, Ondokuz MayÄ±s University, Samsun, Turkey; 2Department of Child and Adolescent Psychiatry, Medical Faculty of Istanbul, Istanbul University, Istanbul, Turkey; 3Department of Child and Adolescent Psychiatry, Dr Sami Ulus Children's Hospital, Ankara, Turkey; 4Department of Child and Adolescent Psychiatry, Faculty of Medicine, Harran University, Sanliurfa, Turkey; 5Department of Child and Adolescent Psychiatry, Faculty of Medicine, Ondokuz MayÄ±s University, Samsun, Turkey Objective: We aimed to determine distribution and diversities of psychiatric comorbidities in children and adolescents with attention deficit/hyperactivity disorder (ADHD) in terms of age groups, sex, and ADHD subtype. Materials and methods: The sample included 6–18 year old children and adolescents from Turkey (N=108; 83 boys, 25 girls) diagnosed with ADHD. All comorbid diagnoses were determined based on the Kiddie Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version assessment. Results: 96.3% of the cases were found to have at least one psychiatric comorbid diagnosis. The most frequent psychiatric comorbid disorder was oppositional defiant disorder (69.4%) followed by anxiety disorders (49%) and elimination disorders (27.8%). Disruptive behavior disorders were more common in ADHD-combined type. Depression and anxiety disorders were more common in girls. Separation anxiety disorder and elimination disorder were more common in children, whereas depression, bipolar disorder, obsessive–compulsive disorder, and social phobia were more common in the adolescents. Conclusion: According to our results, when a diagnostic tool was used to assess the presence of comorbid psychiatric disorders in children and adolescents diagnosed with ADHD, almost all cases had at least one comorbid diagnosis. Therefore, especially in the clinical sample, ...